Stem Biomass Equation of Eucalyptus urophylla S.T. Blake - Melewanto Patabang; Julianus Dising; Adrin Adrin; Aah Ahmad Almulqu (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2020)
Eucalyptus urophylla is one of the typical plants of the Province of East Nusa Tenggara, Indonesia whose distribution includes the islands of Timor, Alor, Wetor, Flores, Adonara, Lomblen, and Pantar. The best land for the growth of E. urophylla is an area with rainfall above 1000 mm every year. E. urophylla dominate the island of Timor hence the potential to absorb carbon and store it in biomass as part of climate change mitigation. This study aims to determine the allometric equation model to predict the potential of E. urophylla stem biomass. Calculation of the amount of stem biomass based on allometric equations is an analytical method used in this study. The sample trees used in equation modeling is 100 trees as a result of the inventory. The equations that can be used to estimate the biomass potential of the stem of E. urophylla in Timor Island were ln = -2.12 + 2.472 ln ( ) and (R2= 0.98); ln = -3.617 + 1.046 ln and (R2= 0.99); and ln = -3.510 + 2.157 ln ( ) + 0.983 ln and (R2= 0.99). The stem biomass potential with the model I amounting to 276.877 tons ha-1, model II of 279.671 tons ha-1, and model III of 280.209 tons ha-1.